Factors associated with the market availability of systemic anti-infective products in Thailand (no. 743) - Siriporn Burapadaja (2018)
Background: Despite the fact that the market availability of medicines has been recognized as one of the most important components in the health-care system, its association with other factors is still in doubt. Objective: This study aimed at determining the factors associated with the number of trade names and products of systemic anti-infective medicines available for the market in Thailand. Methods: A cross-sectional study on the data from the Thai National List of Essential Medicines (Thai EML) 2008 and Thailand Index of Medical Specialties 2008 was undertaken. Results: Results showed a total of 702 trade names and 1,262 products from 137 generic drugs. Half of the products belonged to the classes of beta-lactam antibacterials (39%) and quinolone antibacterials (11.3%). The significant factors found were dosage forms of medicines, manufacturer types and category. The generic drugs that were prepared in more than one dosage form, produced by local manufacturers and categorized as essential medicines (EMs) would have a greater number of trade names and products than those done in one dosage form by foreign manufacturers and as non-EMs. Conclusion: There are at least three factors associated with the number of trade names and products of systemic anti-infective medicines, which include dosage forms of medicines, manufacturer types and EM category. These factors have involved the technical issue, private sector and Thai EML. One suggestion from this finding is to use the Thai EML as a means to control the market availability of systemic anti-infective products in the country. © 2009 Springer-Verlag.